Kinerja Layanan dan Kepuasan Nasabah Masa Pandemi Covid-19 Pada Bank BNI Cabang Bogor - Prasetya, Syarief Gerald; Wardhani, Yustiana (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
The research is aimed at describing service quality and customer satisfaction with PT Bank BNI services during the COVID-19 pandemic. The study used 60 customers to be selected randomly as samples. The analysis method uses Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the analysis found that the performance of services provided by PT Bank BNI Bogor Branch has been able to meet the interests of customers by 83.07%. Then it is known that several attributes are the main priority because their performance is still below the interests of customers, namely the queuing system during the Covid-19 pandemic, the speed of customer service during the Covid-19 pandemic, bank operational schedules during the Covid-19 pandemic, guarantees of getting quality service. the Covid-19 pandemic, the completeness of the facilities/equipment provided, the alertness to customer complaints during the Covid-19 pandemic, the speed in resolving the Covid-19 pandemic problems, the readiness to overcome queues during the Covid-19 pandemic and the readiness of officers when needed. From the results of the CSI analysis, it is known that the level of customer satisfaction is 77.61% which is included in the satisfied category. Thus the services provided by PT Bank BNI Bogor Branch during the Covid-19 pandemic can be said to be good but they still have to continue to make improvements so that their service performance is getting better.